Digital Signal Processing in Experimental Research Volume 1 : Fast Transform Methods in Digital Signal Processing. - Yaroslavsky, Leonid (Digital Signal Processing in Experimental Research, 2., 2011)
This ebook covers fast transform algorithms, analyses, and applications in a single volume. It is the result of the collaboration by the author with others in the world wide university community and has been accumulated over the author's working lifetime of about 40 years. It has now culminated in a nice mix of theoretical development and practical uses of various fast transforms. Thus readers will find practical approaches not covered elsewhere for the design and development of fast transform methods. Some of the most immediate applications, such as detection and analysis of periodicities in.